Gymnastics Education Teaching Learning: A Review of the Literature - Indrayogi; Yudha, Brio Alfatihah Rama; Suryadin, Tatang; Rudi (Universitas Negeri Surabaya, 2026)
Purpose: This study examines the development of teaching and learning practices in gymnastics education within physical education by identifying pedagogical approaches, technology integration, teacher competence, and implementation challenges. Unlike previous reviews focusing mainly on performance aspects, this study provides a multidimensional synthesis of pedagogical, psychological, technological, and cognitive perspectives. Materials and Methods: This study employed a systematic literature review following PRISMA guidelines, including identification, screening, eligibility, and inclusion stages. Data were collected from the Scopus database using structured keywords within the publication range of 2015–2025. A total of 88 records were identified, and 17 articles met the inclusion criteria for final analysis. The selected studies were analyzed thematically to classify key themes related to pedagogy, technology integration, teacher competence, psychological aspects, and learning outcomes. Result: The findings revealed five major themes: pedagogical approaches, technology integration, teacher competence, psychological and inclusivity aspects, and physiological and cognitive impacts. Innovative methods such as Teaching Personal and Social Responsibility (TPSR) and cooperative learning improved students’ motor skills, knowledge, and social attitudes. Technology integration through Android-based media, 3D simulations, and artificial intelligence increased engagement and movement understanding. However, challenges remain, including limited teacher readiness, inadequate facilities, and students’ fear and low confidence. Gymnastics education also contributes to cognitive development, particularly critical thinking skills. Conclusion: Gymnastics education has evolved into a multidimensional and student-centered learning process integrating pedagogy and technology to optimize physical and cognitive learning outcomes.